Distance-to-Time Conversion Using Gompertz Model Reveals Age-Dependent Aerenchyma Formation in Rice Roots - Yamauchi, Takaki (Plant Physiol, 2020)
Distance-to-time conversion by using the Gompertz model compensates for the differences in root elongation rates among different genotypes and conditions, and reveals age-dependent aerenchyma formation.